How to incentivize farmers to adopt and recycle high-standard plastic mulch in China: economic subsidies, government regulations or social norms? - Xie, Xianxiong; Wang, Haoyang; Zhang, Siyang; Liu, Yang (Frontiers in Environmental Science, 2025)
The extensive application of ultrathin plastic mulch in China has resulted in soil degradation, declining crop yields, and the accumulation of microplastic pollution, thereby threatening both sustainable agricultural development and ecosystem health. Consequently, fostering the adoption and recycling of high-standard plastic mulch (HSPM) through economic subsidies and regulatory measures has become imperative. Based on survey data from 635 farmers in Gansu Province and econometric analysis, this study finds that subsidies, regulation, and social norms significantly increase HSPM adoption by 13.03%, 11.66%, and 6.18%, respectively, and recycling by 7.02%, 20.12%, and 11.02%. These measures also exhibit interactive effects: subsidies and norms are complementary, and norms may substitute for regulation. Further, incentive effects are heterogeneous. Subsidies are less effective for smallholders but more effective for low-income, nonpolitically affiliated farmers. Regulations and norms are more effective for high-income, politically affiliated farmers, with social norms showing particular promise in motivating smallholders.